Improvement in wear and corrosion resistance of Ti(C, N)-based cermets via Aluminum nitride additions. (October 2019) - Xu, L.W.; Lin, N.; Zhao, L.B.; Ma, C.; Wang, Z.Y.; He, Y.H.
Abstract: The effects of AlN addition on mechanical properties, wear resistance and corrosion resistance of Ti(C, N)-based cermets are investigated by scanning electron microscope, X-ray diffraction, mechanical properties testing, abrasion testing and Tafel extrapolation. The results show that the appearance of Al element in binder phase may reinforce the binder phase of cermet. With increasing AlN additions, the Vickers hardness of cermet increases from 16.34 GPa to 17.60 GPa, and transverse rupture strength of cermet increases firstly and then decreases. Moreover, the extra AlN additions in cermet may reduce the friction coefficient of cermet, improve the wear resistance of materials and extend the service life of cutting tools during machining Inconel 718 nickel-based superalloy. Additionally, the existence of Al element in cermet may enhance the corrosion resistant of materials by inhibiting the corrosion process of binder phase in sodium hydroxide solution. Highlights: The Ti(C, N)-based cermets with a series of AlN additions are fabricated. The AlN additions inhibit the growth of Ti(C, N) particles in the sintering process. The AlN additions enhance hardness and transverse rupture strength obviously. The proper AlN additives may improve the wear resistance and corrosion resistance.